2012
DOI: 10.1111/j.1743-6109.2011.02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Urology Residents Ready to Treat Premature Ejaculation After Their Training?

Abstract: Introduction The management of premature ejaculation (PE) among urology residents (URs) in the era of standard definition and new treatments is unknown. Aim To determine how future urologists currently address PE and to review their adherence to guidelines. Methods A specifically designed survey on the preferred approaches to the treatment of PE was given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…As in other studies, the need for further education and training in sexual health topics was reported by most respondents at all times (medical school, residency, urologist). Swiss general practitioners and urologists expressed their need for continuing education on sexual issues (Platano et al ., ) as well as Spanish urology residents showed an insufficient training in sexual health topics (Lujan et al ., ). Insufficient training was often reported to be a barrier in addressing sexual health issues, which is in accordance with previous studies (Haboubi & Lincoln, ; Ahrendt & Friedrich, ; Alarcão et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As in other studies, the need for further education and training in sexual health topics was reported by most respondents at all times (medical school, residency, urologist). Swiss general practitioners and urologists expressed their need for continuing education on sexual issues (Platano et al ., ) as well as Spanish urology residents showed an insufficient training in sexual health topics (Lujan et al ., ). Insufficient training was often reported to be a barrier in addressing sexual health issues, which is in accordance with previous studies (Haboubi & Lincoln, ; Ahrendt & Friedrich, ; Alarcão et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent survey of urology residents demonstrated that even though approximately 15% of patients presenting to clinics complain of PE, residents still fail to follow the recommendations of current treatment guidelines; this incongruence indicates insufficient training about PE during urology residency programs. 44 It is evident that the needs of PE treatment remain unmet; however, there are many potentially effective management options. 45 Topical anaesthetic creams, selective serotonin reuptake inhibitors (SSRIs) and phosphodiesterase type-5 (PDE-5) inhibitors have been fairly well studied, while newer modalities, such as tramadol and metered-dose aerosol containing topical anaesthetics, require further evidence to support their efficacy.…”
Section: Pe Treatmentmentioning
confidence: 99%
“…No consensus was reached on the treatment of the disease. In a study conducted by Lujan et al, [8] 15% of the patients who were consulting for premature ejaculation were found to have received incorrect treatment and prescription when evaluated according to the guidelines.…”
Section: Discussionmentioning
confidence: 99%